2008
DOI: 10.1203/pdr.0b013e3181732381
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation With Galactooligosaccharides and Inulin Increases Bacterial Translocation in Artificially Reared Newborn Rats

Abstract: Supplementation of formulas with prebiotics enhances the growth of lactate producing bacteria, and fecal lactate, and acetate levels in infants. High concentrations of organic acids in intestinal lumen have, however, been shown to impair the intestinal barrier function. To determine whether stimulating the colonic microbiotal metabolism with prebiotics would impair the neonatal intestinal barrier function, artificially reared rats were fed milk formula with or without a mixture of galactooligosaccharides/inuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
0
22
2
Order By: Relevance
“…In parallel, cecal lactic acid concentration increased significantly, similar to the current study with GOS/inulin. Although FOS impaired the intestinal epithelial barrier function in the original study (9), the present study did not find that colonic permeability was affected (7). The method, however, may not have been sensitive enough to detect a significant difference.…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…In parallel, cecal lactic acid concentration increased significantly, similar to the current study with GOS/inulin. Although FOS impaired the intestinal epithelial barrier function in the original study (9), the present study did not find that colonic permeability was affected (7). The method, however, may not have been sensitive enough to detect a significant difference.…”
contrasting
confidence: 77%
“…The method, however, may not have been sensitive enough to detect a significant difference. Although the original FOS study assessed in vivo chromium ethylenediaminetetraacetate uptake (9), the present study used Ussing chambers and measured the flux of fluorescein isothiocyanate-dextran through nonstripped colon explants (7). The labeled dextran had to cross not only the mucosal barrier, but also submucosa, muscularis externa, and serosa or adventitia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of TJ protein expression did not give more information about mechanisms involved because mRNA levels of ZO-1 and CGN did not correlate with the paracellular permeability (FD-4) variations. However, interpreting variations in ZO-1 mRNA expression in tissues is not as clear as in cell cultures because several authors have already observed variations in ZO-1 mRNA expression but no difference in ex vivo permeability in rats (27) or increase in ileal permeability but increase in ZO-1 mRNA expression (28). Similarly, it is difficult to predict the actual effect of the tendency for upregulation of CGN mRNA in the ileum of HP LBW piglets from the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Among those suggested to have a critical role are luminal factors endogenously produced in the colon, such as microbiota-derived short-chain fatty acids (SCFA). Resulting from the bacterial fermentation of dietary fiber and resistant starch, their concentration after birth progressively increases in the colon in humans and rats (4,29). In particular, we focused our work on the effect of butyrate because this SCFA was shown to enhance the cholinergic phenotype of myenteric neurons and related neuromuscular functions (35,36).…”
mentioning
confidence: 99%